2023
DOI: 10.1136/bmjopen-2022-063462
|View full text |Cite
|
Sign up to set email alerts
|

Codesigning an intervention to strengthen COVID-19 vaccine uptake in Congolese migrants in the UK (LISOLO MALAMU): a participatory qualitative study protocol

Abstract: IntroductionMigrants positively contribute to host societies yet experience barriers to health and vaccination services and systems and are considered to be an underimmunised group in many European countries. The COVID-19 pandemic has highlighted stark inequities in vaccine uptake, with migrants facing access and informational barriers and lower vaccine confidence. A key challenge, therefore, is developing tailored vaccination interventions, services and systems which account for and respond to the unique driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 39 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…to influence the health decision-making process. 48 Our findings align with other research which highlights preferences for face-to-face 58,59 and oral communication 60,61 among migrant populations, as well as strategies that build or reinforce trust. 59,62,63 They also align with systematic reviews that have indicated that culturally adapted interventions may be effective in community settings.…”
Section: Disseminationsupporting
confidence: 90%
See 1 more Smart Citation
“…to influence the health decision-making process. 48 Our findings align with other research which highlights preferences for face-to-face 58,59 and oral communication 60,61 among migrant populations, as well as strategies that build or reinforce trust. 59,62,63 They also align with systematic reviews that have indicated that culturally adapted interventions may be effective in community settings.…”
Section: Disseminationsupporting
confidence: 90%
“…Participants were financially compensated for participation using vouchers (1‐h interviews—£20; 2‐h workshops—£40) and reimbursed in cash for travel costs. Nonacademic coalition members were paid for their time (according to rates set out by NIHR INVOLVE guidance 37 ) and Hackney Congolese Women Support Group and Hackney Refugee and Migrant Forum received financial donations to support their running, in addition to nonfinancial contributions (e.g., skills‐based training) 36 . A community celebration and presentation of key findings was held in July 2022.…”
Section: Methodsmentioning
confidence: 99%
“…This study originated from Congolese migrant community members identifying unmet needs and concerns around COVID-19 vaccination within their community, coupled with the academic partner's interest in exploring existing evidence gaps related to vaccination beliefs and behaviours among migrant populations (38)(39)(40). Within this CBPR study (reported elsewhere (41,42)), qualitative, semistructured in-depth interviews were conducted with Congolese migrants to explore their beliefs, perceptions and lived experiences of migration and healthcare in the UK, the COVID-19 pandemic, and routine and COVID-19 vaccination. The coalition co-designed and pilot-tested the topic guide and jointly decided on the data collection approaches and all aspects of the study design.…”
Section: Methodsmentioning
confidence: 99%
“…Hackney was the 11 th most deprived local authority in England based on the Indices of Deprivation 2015 (45). It is thought to host one of the UK’s larger populations of Congolese migrants (41, 46). A single nationality migrant group was involved for an in-depth, culturally situated understanding of the research topic, although it was recognised the sample differed across a variety of other criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation